The complete chloroplast genome of the Chinese medicinal herb Senecio scandens. Issue 2 (2nd April 2020) - Zheng, Shuning; Wang, Qirui; Gao, Chenshu; Ge, Yuqing; Cheng, Rubin
Abstract: Senecio scandens Buch.-Ham. is a crucial source of Chinese traditional medicine with antibacterial properties. In this study, we report the complete chloroplast genome sequence of S. scandens . The assembled chloroplast genome was 150, 729 bp in length, containing two inverted repeated (IR) regions of 24, 455 bp each, a large single-copy (LSC) region of 83, 984 bp and a small single-copy (SSC) region of 17, 835 bp. The genome encodes 133 genes consisting of 89 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. The overall GC content of S. scandens is 37.4%, with the highest GC content of 43% in the IR region. A total of 38 simple sequence repeats are identified in the cp genome of S. scandens . Phylogenetic analysis demonstrated a sister relationship between S. scandens and Pericallis hybrida, indicating further revisions for the genus Senecio . This work provides basic genetic resources for investigating the evolutionary status and population genetics diversities for this medicinal species.